2011
DOI: 10.4274/npa.y5716
|View full text |Cite
|
Sign up to set email alerts
|

Temel Yas Unsurları Ölçeği Türkçe Formunun Geçerlik ve Güvenirlik Çalışması

Abstract: Objective: The aim of this study was to examine the psychometric features of the Turkish version of The Nurses' Observation Scale for Geriatric Patients (NOSGER), to expose its factor structure and to evaluate its validity and reliability. Methods:The study was carried out among 273 residents (180 women, 93 men; aged 60-96) in a nursing home in Izmir. In the study, the NOSGER, Geriatric Depression Scale (GDS) and the Standardized Mini-Mental Test (SMMT) were used as data collection tools. Internal consistency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The original of the scale was administered to 158 adults with experience of loss, and the Cronbach α coefficient was found to be 0.91. A Turkish validity and reliability study was conducted by Selvi et al (22), and the internal consistency Cronbach α value was found to be 0.94.…”
Section: Core Bereavement Items (Cbi)mentioning
confidence: 99%
“…The original of the scale was administered to 158 adults with experience of loss, and the Cronbach α coefficient was found to be 0.91. A Turkish validity and reliability study was conducted by Selvi et al (22), and the internal consistency Cronbach α value was found to be 0.94.…”
Section: Core Bereavement Items (Cbi)mentioning
confidence: 99%
“…The scale evaluates the physical, emotional, cognitive, and behavioral symptoms experienced by bereaved people. Another widely used scales adapted into Turkish are the 70-item TTBQ (Ayaz et al, 2014), 21-item TRIG (Yildiz & Cimete, 2011), and the 17-item Core Bereavement Items (Selvi et al, 2011). However, none of these tools has been included in the recent diagnostic criteria of PCBD.…”
mentioning
confidence: 99%